Diagnóstico de la calidad de carne de res que se expende en la Ciudad de Calceta - Bermúdez Demera, Yen Henry (2018)
ABSTRACT The present investigation was based on the determination of the hygienic-sanitary quality of the beef sold in provisional stands of meat sale and meat markets in Calceta city by a diagnosis, for which it was established the identification of the sources of contamination in the commercialization of the same through the application of a checklist of fulfillment parameters taking as reference the standard NTE INEN 2687, by which it was determined that the contamination is triggered from the lack of knowledge of the personnel about good commercialization practices and integral waste management, lack of hygiene of the same, inexistent cleaning of work surfaces and work tools , null pest control and presence of physical contaminants. Microbiological analysis were performed to 25 samples (18 kiosks and 7 meat markets) in two periods of time (6:00 and 11:00 am) evidencing an increase in the microbial amount in the analyzed parameters, being Salmonella, total coliforms, Escherichia coli, Staphylococcus aureus and Aerobios Mesophiles, in accordance with the NTE INEN 1338 standard. Generally, only the 16%of the samples could match the aceptable standards. The probabilities of contamination for kiosks were higher than meat markets.